PENGARUH MEDIA PERIKLANAN TERHADAP PENGAMBILAN KEPUTUSAN SISWA SMU UNTUK MENDAFTAR DI UNIVERSITAS KRISTEN MARANATHA: SIKAP KONSUMEN SEBAGAI VARIABEL MODERASI (STUDI KASUS SISWA SMU DI BANDUNG) - Kartika Imasari; Cen Lu (Jurnal Bisnis dan Ekonomi, 2010)
Advertising is one of the indicators to build a brand image in consumers' minds. Advertisingcan evolve through feedback or consumer attitudes toward advertising displayed and the brandimage the company itself. Consumer’s acceptance or rejection of advertising will be veryinfluential on the goods or services offered. Advertising is used as a stimulus to bring the responsefrom consumers. Response referred in this research is the consumer attitude. In this case can beseen that the advertising is basically intended to build an customer’s attitude (affective andcognitive). Purpose of this research is to view the relationship between the effectiveness ofpromotions that have been conducted Maranatha Christian University with purchasing decisionsof high school students in Bandung, which is moderated by consumer attitudes. The resultsobtained show that high school students' attitudes toward advertising and Maranatha ChristianUniversity itself have a good results as well as feelings of respondents toward advertising showsthat advertising is able to remind, made an impression and encouraging respondents to continuetheir education at Maranatha Christian University.Keywords: advertising attitude, consumer attitude, purchasing decision, marketing mix,advertising media